Digital logistics as a tool for minimizing logistics risks in the activities of pharmaceutical enterprises - Lisna, Anastasia; Posilkina , Olha; Litvinova , Olena (Annals of Mechnikov’s Institute, 2024)
Introduction. Today, pharmaceutical supply chains form the basis of the pharmaceutical market, fueling trade, consumption, and economic growth. Trends such as digitalization, saving processes, and the geographical concentration of pharmaceutical production have made pharmaceutical supply chains more efficient but also changed their risk profile. Most pharmaceutical companies currently use risk management strategies that address local violations. Nevertheless, global experience in pharmaceutical supply chain management and strategic planning suggests that risks beyond the control of individual enterprises can have unpredictable consequences that cannot be mitigated by the efforts of one enterprise. That is why the introduction and development of digital technologies that have significant potential to minimize and prevent risks, in particular in the logistics activities of pharmaceutical enterprises, is an urgent topic of our time. Aim. The aim of the study was to analyze the prospects of digitalization of logistic processes at pharmaceutical enterprises to minimize and eliminate logistic risks in an unstable external environment for the timely provision of necessary and high-quality pharmaceutical products to the population. Materials and methods. To achieve the aim of the study, foreign and domestic scientific literature on pharmaceutical logistics was analyzed. Research methods are informational, retrospective, graphic, statistical, and logical. Results and discussion. The relevance of digitalizing the logistics activities of pharmaceutical enterprises and pharmaceutical supply chains to improve their reliability and safety has been substantiated. Trends in the development of logistics that will shape the future of the pharmaceutical industry have been identified. The risks associated with the introduction of digital technologies into the logistics activities of pharmaceutical enterprises are identified. A review of methods of managing digital risks in the logistics activities of pharmaceutical enterprises was conducted. An algorithm for risk management in the digital transformation of business processes in the logistics activity of pharmaceutical enterprises is proposed. Conclusion. It is proven that a certain potential and experience of using digital technologies have already been accumulated in domestic pharmacy, which opens up serious innovative prospects for minimizing and preventing risks, in particular in the logistics activities of pharmaceutical enterprises. The COVID epidemic and military action highlighted the weaknesses of domestic pharmaceutical logistics. And it is the active introduction of digital technologies into the logistics activities of pharmaceutical enterprises that will contribute to their successful solution. Undoubtedly, the issue raised in this study does not fully address the complex array of questions related to the implementation of scientific and practical approaches to risk management resulting from the application of digital technologies in the logistical activities of pharmaceutical enterprises and pharmaceutical supply chains. Unresolved are a set of issues associated with substantiating the mechanism for managing the risks of digital transformation of logistical business processes, developing a methodology for assessing the effectiveness of managing digital risks in the logistical activities of pharmaceutical enterprises, and others, which will define the prospects for our further research. Keywords: pharmaceutical enterprise, pharmaceutical supply chain, pharmaceutical market entities, digitalization, digital risks.